Association analysis of pulmonary tuberculosis and vitamin D Receptor Gene Polymorphisms of Han population in Western China. (December 2021) - Xu, Shaohua; Xie, Xiaoxia; Jiao, Lin; Bai, Hao; Wu, Xi; Ying, Jun; Ying, Binwu
Abstract: Objective: To investigate the associations between single nucleotide polymorphism (SNP) of vitamin D receptor (VDR) gene and tuberculosis (TB) infection risk. Methods: 597 newly diagnosed pulmonary tuberculosis (PTB) patients from the Han population in Western China were randomly selected while 901 healthy subjects were divided into control group from September 2015 to September 2018. In the case-control study, 21 SNPs within the VDR gene were genotyped. Use SPSS 19.0 statistical software, SNP statistical software (Plink) and Pub-med network database to analyze the correlation between VDR SNP and PTB susceptibility. Results: The 14 SNPs of VDR gene screened in the experiment were consistent with the frequency of PTB-related and minor alleles> 5% in HapMap Asian population. Three SNPs (rs58379944, rs11574012, rs12581281) were correlated with PTB by x 2 analysis. The rs58379944, rs11574012 alleles "G" and rs12581281 alleles "A" in genotype analysis were susceptible to tuberculosis. In the genotype analysis, allele "G" of rs58379944 and rs11574012 and allele "A" of rs12581281 provided protection against PTB infection. Conclusion: rs58379944, rs12581281 and rs11574012 allelic variants in VDR gene were found to be closely associated with PTB infection in the Han population in Western China. The protection it achieved may be one of the reasons for reducing the infection rate. Highlights: The first analysis between Vitamin D Receptor Gene Polymorphisms and PTB predisposition and its clinical traits in Western Chinese Han population. The statistical analysis between candidate 3 SNPs (rs58379944, rs12581281, rs11574012) and phenotypes of PTB were conducted. rs58379944, rs11574012 alleles "G" and rs12581281 alleles "A" in genotype analysis were susceptible to tuberculosis. Polymorphisms of VDR can fight PTB infection and decrease the infection risk of Han population in Western China.